Increasing sales volume with a marketing mix strategy using swot analysis on a bread sourdough bakery - Dyah Ika Kirana Jalantina; Maria Magdalena Minarsih (SEAN Institute, 2024)
A Bread Sourdough Bakery is a manufacturer and shop that sells sourdough bread products, where sourdough is a type of bread that is currently starting to be popular with consumers because the raw materials are considered more natural and healthy than bread on the general market. Determining a marketing mix strategy for this business is one of the strategies for developing, improving the business and facing intense competition. The aim of this research is to find out whether the aspects of the marketing mix strategy, namely product, price, place, promotion, people, physical evidence and process, are appropriate and can be applied to increase sales volume. This research is a qualitative descriptive study, data was collected directly from the company by conducting observations and interviews. The research results show that the marketing mix strategy implemented can increase sales volume so that the Bread Sourdough business owner must continue to improve existing strategies in order to win the competition.